2015
DOI: 10.1016/j.neuroscience.2015.05.056
|View full text |Cite
|
Sign up to set email alerts
|

An endocannabinoid system is present in the mouse olfactory epithelium but does not modulate olfaction

Abstract: Endocannabinoids modulate a diverse array of functions including progenitor cell proliferation in the central nervous system, and odorant detection and food intake in the mammalian central olfactory system and larval Xenopus laevis peripheral olfactory system. However, the presence and role of endocannabinoids in the peripheral olfactory epithelium has not been examined in mammals. We found the presence of cannabinoid type 1 (CB1) and cannabinoid type 2 (CB2) receptor protein and mRNA in the olfactory epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 85 publications
(123 reference statements)
0
26
1
Order By: Relevance
“…Previous studies have shown that human ON cells exhibit a neuronal phenotype comprising several types of receptors including 5-HT 2C receptors and signaling pathways related to olfaction and other functional aspects of the CNS [16]. Likewise, expression of CB1R and the endocannabinoid, 2-arachidonylglycerol has been found in the ON of experimental animals [17,18]. Although alterations in CB1R levels have been described in the brain of cannabis users [19][20][21][22], and changes in endocannabinoid levels are detected in plasma following the administration of THC to healthy volunteers [23,24], no data has been provided yet regarding changes in 5HT2AR at central or peripheral level in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that human ON cells exhibit a neuronal phenotype comprising several types of receptors including 5-HT 2C receptors and signaling pathways related to olfaction and other functional aspects of the CNS [16]. Likewise, expression of CB1R and the endocannabinoid, 2-arachidonylglycerol has been found in the ON of experimental animals [17,18]. Although alterations in CB1R levels have been described in the brain of cannabis users [19][20][21][22], and changes in endocannabinoid levels are detected in plasma following the administration of THC to healthy volunteers [23,24], no data has been provided yet regarding changes in 5HT2AR at central or peripheral level in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they found that the production of endocannabinoids depends on the hunger state of the animal, which is responsible for changes in odor sensitivity activity. Similarly, CB1 receptors were also found in the OSN of rodents [27]. The CB1 receptor agonists changed odorant-induced cellular activity, but the authors did not observe olfactory consequences in the behavior of mutant mice lacking CB1 receptors (CB1-KO; [27]).…”
Section: The Endocannabinoid System In the Olfactory Epitheliummentioning
confidence: 99%
“…Similarly, CB1 receptors were also found in the OSN of rodents [27]. The CB1 receptor agonists changed odorant-induced cellular activity, but the authors did not observe olfactory consequences in the behavior of mutant mice lacking CB1 receptors (CB1-KO; [27]). Despite the species differences, several divergences appear between these studies.…”
Section: The Endocannabinoid System In the Olfactory Epitheliummentioning
confidence: 99%
See 2 more Smart Citations